Influence of Resistance and Plyometric Training Modalities on Psychomotor Variables and Playing Ability among Competitive Cricket Players - Mukhtar Ahmad Wani; Dr. Vikas Saxena (Journal of International Islamic Law, Human Right and Public Policy, 2025)
This study examines the effects of resistance training and plyometric training modalities on specific psychomotor variables and playing proficiency among competitive cricket players. To be good at modern cricket, you need to be technically good, but you also need to be very coordinated, quick to react, and have good neuromuscular efficiency. Resistance and plyometric training are commonly employed in athletic conditioning; however, empirical evidence contrasting their impacts on psychomotor performance and cricket playing ability is scarce. An experimental design was employed, wherein sixty male competitive cricket players aged 18–25 years were randomly allocated to a resistance training group, a plyometric training group, and a control group. The experimental groups participated in an eight-week structured training regimen, whereas the control group engaged in standard practice. We looked at psychomotor variables like reaction time, hand-eye coordination, balance, agility, and speed, as well as standardized tests of playing ability. Using ANCOVA to analyze the data, we found that both experimental groups had big improvements in psychomotor variables and playing ability compared to the control group. The plyometric training group had the biggest improvements in agility, reaction time, and playing performance. The results indicate that incorporating plyometric and resistance training into cricket conditioning programs can significantly improve psychomotor efficiency and overall playing performance.